The Effect of Photobiomodulation on Sperm Parameters and Apoptosis in an Experimental Testicular Torsion Model: Photobiomodulation in experimental testicular torsion - Torabi, Ruhollah; Azarbarz, Nastaran; Bayat, Mohamad; Bayatiani, Mohamadreza; Barzroodi Pour, Mitra (Journal of Lasers in Medical Sciences, 2025)
Introduction: As a serious urological emergency, testicular torsion (TT) results in ischemia and oxidative stress, negatively impacting sperm function and potentially causing persistent infertility. This research seeks to evaluate the efficacy of photobiomodulation (PBM) therapy as a viable therapeutic intervention for the condition of testicular torsion. Methods: Male NMRI mice (n=24) were classified into four distinct experimental groups: I) Control, II) laser (L), III) Torsion (T), IV) Torsion accompanied by laser intervention (T&L). We induced testicular torsion by rotating both testes 720° in a counterclockwise direction, and then, after 2 hours, detorsion was performed. In the T&L group, following the torsion induction, the mice’s testes underwent laser irradiation at a wavelength of 808 nm (0.03 J/cm²) for 21 days. Post-sacrifice dissection of the testes and epididymis was performed for additional examination. Results: Sperm motility was significantly higher in the laser-treated group relative to the T group. Furthermore, microscopic evaluation indicated that the T&L group exhibited greater spermatogonia and Leydig cell counts, as well as enlarged seminiferous tubule diameter and thicker epithelium compared to the T group. Conclusion: On the basis of the present findings, laser therapy can mitigate complications from testicular torsion and improve sperm motility and testicular histopathology.